2019
DOI: 10.3390/pathogens8030141
|View full text |Cite
|
Sign up to set email alerts
|

Oral Inoculation of Specific-Pathogen-Free Chickens with Chicken Anemia Virus Induces Dose-Dependent Viremia and Transient Anemia

Abstract: Chicken infectious anemia caused by chicken anemia virus (CAV) is a very important immunosuppressive disease in chickens. The horizontal spread of CAV in field chickens has been confirmed mainly through oral infection in our published article. Anemia is the main symptom of this disease. Studies by other scientists have shown that infection of CAV in 1-day-old chicks can cause anemia, and the degree of anemia is directly proportional to the dose of infectious virus. However, the pathogenesis of oral inoculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Besides, CAV was positive in each detected tissue organ from 7 to 21 dpi. Moreover, our study found that the viral load in thymus was highest in the infection group compared with other organ tissues ( 16 , 22 ). The above results suggested that CAV is highly susceptible to infection of central immune organs including thymus and bursa.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Besides, CAV was positive in each detected tissue organ from 7 to 21 dpi. Moreover, our study found that the viral load in thymus was highest in the infection group compared with other organ tissues ( 16 , 22 ). The above results suggested that CAV is highly susceptible to infection of central immune organs including thymus and bursa.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, marked changes were also observed in the hematological parameters and histopathological changes at 14 dpi. Specifically, there was a significant decrease in the PCV of infected chickens at 14 dpi ( 22 ). Severe atrophy of thymus and bursa, mild to moderate atrophy of spleen, and pale bone marrow were observed in infected chickens at 14 dpi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hematological profile of the infected groups showed hypochromic anemia characterized by a decrease in PCV, erythrocyte count, and hemoglobin content, which could potentially be attributed to the direct link to the virus's direct effect on the bone marrow, resulting in aplasia and a detrimental impact on the erythrocytic and granulocytic lineages of bone marrow cells, consequently affecting erythropoiesis and myelopoiesis [34]. The leukocytic finding of infected groups showed leukocytopenia, which could be attributed to the fact that the primary cells affected during CAV infection's progression involve hematopoietic progenitor cells in the bone marrow and thymic precursor cells in the thymus cortex [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that lymphoid tissues are the primary targets for CIAV infection, and CIAV persists in thymic lymphocytes where it cannot be neutralized by the antibody ( Cardona et al., 2000 ; Markowski-Grimsrud and Schat, 2003 ; Tongkamsai et al., 2019a ). Continuous dissemination of the virus from the thymus with insufficient antibody response and the release of infected cells from the thymus into blood circulation might be the cause for the increased virus distribution in the other tissues ( Tongkamsai et al., 2019b ). Subsequently, CIAV can be replicated in the secondary tissues, and transmitted through horizontal contact or vertical transmission via hatching eggs.…”
Section: Discussionmentioning
confidence: 99%